2014
DOI: 10.1136/bjophthalmol-2014-304948
|View full text |Cite
|
Sign up to set email alerts
|

Posterior iris-claw aphakic intraocular lens implantation and Descemet membrane endothelial keratoplasty

Abstract: NCT02020044.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
(32 reference statements)
2
21
0
3
Order By: Relevance
“…Previous studies have demonstrated rapid visual rehabilitation after combining DSAEK with phacoemulsification and IOL implantation [4, 5]. Moreover, the combination of EK with iris-claw IOL implantation has also been described [68]. Karimian and Sadoughi [6] presented the successful combination of DSAEK with retropupillary iris-claw IOL implantation in patients with corneal edema and aphakia or with AC-IOL; in the pseudophakic case, the AC-IOL was exchanged with the iris-claw IOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated rapid visual rehabilitation after combining DSAEK with phacoemulsification and IOL implantation [4, 5]. Moreover, the combination of EK with iris-claw IOL implantation has also been described [68]. Karimian and Sadoughi [6] presented the successful combination of DSAEK with retropupillary iris-claw IOL implantation in patients with corneal edema and aphakia or with AC-IOL; in the pseudophakic case, the AC-IOL was exchanged with the iris-claw IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, endothelial keratoplasty (EK) in the form of Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasty (DMEK) has become the standard of care for the treatment of endothelial decompensation [13]. Several studies have reported the successful combination of EK with cataract surgery or alternatively with iris-claw intraocular lens (IOL) implantation [48]. In this report, we present the successful management of a case with coexistent traumatic mydriasis, aphakia and corneal edema with a triple procedure of simultaneous pupilloplasty and retropupillary iris-claw IOL implantation combined with DSAEK.…”
Section: Introductionmentioning
confidence: 99%
“…Die optimale Platzierung der IFIOL wird fortlaufend diskutiert, und je nach Studie wird eine prä-oder retropupilläre Platzierung empfohlen [25]. Bezüglich der Endothelzelldichte zeigt sich bei retropupillärer Implantation auch nach über 5 Jahren kein statistisch signifikanter Abfall [26,27]. In einem rezenten Vergleich von 87 Augen mit präpupillärer und 93 Augen mit retropupillärer IFIOL-Fixation zeigte sich kein statistisch signifikanter Unterschied in der Endothelzelldichte nach 5 Jahren (Abb.…”
Section: Irisfixierte Linse (Ifiol)unclassified
“…Choragiewicz und Kollegen [12] berichten von Druckanstiegen auf bis zu 24 mmHg, bedingt durch die nahtlose Technik. Auch bei simultan durchgeführter Hornhauttransplantation wird in der Literatur [13,14] von guten postoperativen Befunden berichtet.…”
Section: Ergebnisseunclassified